The Effect of Social Media, Flash Sales, and Islamic Lifestyle on Impulsive Buying Behavior on The Shopee Platform - Nur Salsabila; Rahmadani Rahmadani; Marlya Fatira; Rizal Agus (Politeknik Baubau, 2026)
This research aims to determine the influence of social media, flash sales, and Islamic lifestyle on impulsive buying behavior on the Shopee platform (a study on Muslim students at Medan State Polytechnic). In this study, the independent variables are social media, flash sales, and Islamic lifestyle, while the dependent variable is impulsive buying behavior. The sample used in this study consisted of 150 Muslim student respondents from Medan State Polytechnic who use the Shopee platform, with data collected through questionnaires as primary data and secondary data derived from theoretical studies in books and journals. This study employs a quantitative method with data collection techniques through questionnaires evaluated using a Likert scale, validity testing, and reliability testing. The prerequisite tests include normality test, multicollinearity test, and heteroscedasticity test. The data analysis technique used to answer the hypothesis employs multiple linear regression analysis, partial test (t), simultaneous test (F), and coefficient of determination test (R2) with a significance level of 5% (α=0.05), processed with the assistance of SPSS 25. The results of this study indicate that the social media variable has a positive and significant effect on the impulsive buying behavior of Muslim students at Politeknik Negeri Medan on the Shopee platform, the flash sale variable has a positive and significant effect on the impulsive buying behavior of Muslim students at Politeknik Negeri Medan on the Shopee platform, and the Islamic lifestyle variable has a negative and significant effect on the impulsive buying behavior of Muslim students at Politeknik Negeri Medan on the Shopee platform. The social media, flash sale, and Islamic lifestyle variables have a significant effect on the impulsive buying behavior of Muslim students at Politeknik Negeri Medan on the Shopee platform).